1994
DOI: 10.1111/j.1745-4557.1994.tb00140.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Sensory Quality Attributes and Kernel Chemical Composition of Fresh‐frozen Sweet Corn

Abstract: Knowledge of relationships between kernel composition and sensory attributes of sweet corn could be helpful in selection of corn genotypes for the food industry. Frozen samples of four shrunken2 sweet corn inbred lines and two commercial hybrids were assayed for dimethyl sulfide (DMS), phytoglycogen and sugar concentrations. Sensory evaluation of the same samples by a trained descriptive panel was conducted to determine intensity of attributes of the three main components of sweet corn quality (aroma, flavor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
2

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 18 publications
4
32
0
2
Order By: Relevance
“…One common approach is to conduct a multiple regression of individual sensory attribute ratings against overall liking (e.g. Rasekh et al, 1970;Powers et al, 1977;Azanza et at., 1994). If the attribute ratings have been normalized, the obtained coefficients of the equation will index the degree of importance of the attribute to overall liking.…”
Section: Relative Importance Of the Senses To Food Acceptancementioning
confidence: 99%
“…One common approach is to conduct a multiple regression of individual sensory attribute ratings against overall liking (e.g. Rasekh et al, 1970;Powers et al, 1977;Azanza et at., 1994). If the attribute ratings have been normalized, the obtained coefficients of the equation will index the degree of importance of the attribute to overall liking.…”
Section: Relative Importance Of the Senses To Food Acceptancementioning
confidence: 99%
“…By determining which product sensory attributes are most important to consumers, we can focus development efforts on satisfying their expectations (8). Knowledge of relationships between food composition and sensory attributes has been helpful in selection of better sweet corn genotype for the food industry (9), in prediction of sensory quality from physico-chemical measurements in frozen peas (10), or simply in the commercial classification of canned grapefruit based on analytical and sensory properties (11). The main purpose of this paper was to study the physical and chemical changes in two varieties of green bean to predict their maturity level.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of fresh, or processed whole kernels, canned or frozen, is determined by its unique combination of flavour, texture and aroma (Lertrat and Pulam, 2007). Sweetness is the major component of flavour and affected by the amounts of sugar and starch in the endosperm (Flora and Wiley, 1974;Azanza et al, 1994). It has been reported that selection for more tender and crispy genotypes with higher sugar and lower starch concentration and an increased sweet corn aroma would increase the eating quality of the product (Azanza et al, 1996).…”
Section: Introductionmentioning
confidence: 99%